Anti-inflammatory effects of Glycine tabacina extract in LPS-stimulated macrophages and collagen-induced arthritis mice. (November 2019) - Tu, Yanbei; Wang, Kai; Wan, Jian-Bo; He, Chengwei
Graphical abstract: Highlights: G. tabacina extract (GTE) inhibited inflammatory mediators expression in vitro . GTE blocked the activation of NF-κB and MAPK pathways in macrophages. GTE ameliorated the arthritic symptoms in collagen-induced arthritis mice. Nine isoflavonoids were identified in GTE by UHPLC-DAD-MS/MS analysis. Abstract: Glycine tabacina (Labill.) Benth, a renowned Chinese medicinal herb, has been used for treatment of rheumatoid arthritis (RA) and joint infection. This study aimed to investigate inhibitory effect of its ethanol extract (GTE) on RA-associated inflammation. Nine isoflavonoids of twelve ones which were found in G. tabacina roots were identified by UHPLC-DAD-MS/MS. GTE treatment suppressed lipopolysaccharide-stimulated overproduction of nitric oxide, TNF-α and IL-6, and iNOS expression in macrophages. GTE blocked the activation of NF-κB and MAPK pathways, as indicated by reduced levels of phosphorylation of IKKα/β, IκBα, p38, ERK and JNK, and the suppressed nuclear translocation of NF-κB p65. Additionally, GTE administration decreased swelling of arthritic paw and serum TNF-α and IL-1β levels in collagen-induced arthritis (CIA) mice. These results demonstrated that GTE exhibited strong anti-inflammatory and anti-arthritic activities through suppressing NF-κB and MAPK pathways activation in activated macrophages and CIA mice, suggesting the potential applications of this species in RA prevention and treatment as functional food or therapeutic agent.